Novel non‐contiguous exon duplication in choroideremia. Issue 1 (19th April 2017) - Edwards, T.L.; Williams, J.; Patrício, M.I.; Simunovic, M.P.; Shanks, M.; Clouston, P.; MacLaren, R.E.
Abstract : The importance of establishing a genetic diagnosis in patients with a choroideremia phenotype has been underscored by the advent of gene replacement therapy for this condition. Here, we describe a complex imbalance at the CHM locus in a male patient with classical disease. At the DNA level, this imbalance consists of 2 non‐contiguous duplications (exons 1‐2 and 9‐12). Further characterization suggests the generation of 2 independent CHM transcriptional units, one of which may produce a deleted form of the Rab escort protein 1 protein. Expression of such a type of aberrant protein in photoreceptors may have important implications when considering gene therapy for this disorder. Abstract :